AN ENHANCEMENT PROCESS FOR GRAY-SCALE IMAGES RESULTED FROM IMAGE FUSION USING MULTIRESOLUTION AND LAPLACIAN PYRAMID - C Rama Mohan; A Ashok Kumar; S Kiran; Vasudeva (ICTACT Journal on Image and Video Processing, 2021)
The main issue with the multi-focus images lies in obtaining the relative information about the identification of objects in the individual images with less resolution. Hence the image fusion methods have attracted attention to obtain high resolute image with a pair of multifocus images. An attempt has been made in the present work to develop an image fusion methodology designing on multiresolution for the feature extraction and for better morphological details, the paper discussed about the Laplacian pyramid algorithm. Five sets of multifocus images obtained with different formats have been introduced to the sixteen different image fusion algorithms including the proposed method. Various statistical metrics were evaluated for each image fusion method. The careful comparison of the visual and objective metrics reveals that the proposed method shows best performance with not only having visual quality and also confirmed based on the variation of the statistical metrics.